1 0 1 3 1 5 − x + 1 0 3 3 1 3 − x + 1 0 5 3 1 1 − x + 1 0 7 3 0 9 − x = − 4
Find the positive integer x that satisfies the above equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
excellent!
− 1 + − 1 + − 1 + − 1 = − 4 so just set the first term equal to -1 and solve for x 1 0 1 3 1 5 − x = − 1 − 1 0 1 = 3 1 5 − x x − 3 1 5 = 1 0 1 x = 3 1 5 + 1 0 1 = 4 1 6
I also solved it this way :)
Just try for 315 - x = -101 first,
x = 416;
-1 - 1 - 1 - 1 = 4 is found true with x = 416.
I've also done this problem in same manner. It is quicker method than other.
A bit confused @ the processs to get the solution. However I took the more complex process and received x = 416
But its more like a guess....any general solution...
I find the longest way x=1870908416/4497376=416, i never thought other simpilified method by adding 4 in left equation
[SOLUTION 1]
let (315-x)/101 = -1 => x=416
then for x=416, (313-x)/103 = -1, (311-x)/105 = -1 and , (309-x)/107 = -1 therefore [x=416].
[SOLUTION 2]
if we see that
315 + 101 = 416
313 + 103 = 416
311 + 105 = 416
and
309 + 107 = 416
this implies that x=416
omg,why I never realize that?I kept on thinking how to count to find x but it turns out to be answer in front of me.lol!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Zero Product Property
I have a neat solution to this problem. Just add 1 to each and every term on the left side. To keep balance, add 4 to the right side. Simplifying will yield that x = 4 1 6 .
1 0 1 3 1 5 − x + 1 0 3 3 1 3 − x + 1 0 5 3 1 1 − x + 1 0 7 3 0 9 − x ( 1 0 1 3 1 5 − x + 1 ) + ( 1 0 3 3 1 3 − x + 1 ) + ( 1 0 5 3 1 1 − x + 1 ) + ( 1 0 7 3 0 9 − x + 1 ) 1 0 1 4 1 6 − x + 1 0 3 4 1 6 − x + 1 0 5 4 1 6 − x + 1 0 7 4 1 6 − x ( 4 1 6 − x ) ( 1 0 1 1 + 1 0 3 1 + 1 0 5 1 + 1 0 7 1 ) = = = = − 4 − 4 + 4 0 0
By zero product property ,
4 1 6 − x = 0 ⇒ x = 4 1 6 .